2022
DOI: 10.1007/s00406-022-01430-8
|View full text |Cite
|
Sign up to set email alerts
|

Positive schizotypy is associated with amplified mnemonic discrimination and attenuated generalization

Abstract: Tendency to experience inaccurate beliefs alongside perceptual anomalies constitutes positive schizotypal traits in the general population and shows continuity with the positive symptoms of schizophrenia. It has been hypothesized that the positive symptomatology of schizophrenia, and by extension, the odd beliefs and unusual perceptual experiences in the general population, are associated with specific alterations in memory functions. An imbalance between memory generalization and episodic memory specificity h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…We did not observe similar deficits with positive schizotypy, or in the interactions of positive schizotypy with the other dimensions. This is in contrast to Vass et al (2022), but consistent with our previous finding that hippocampal volume and episodic memory deficits were not associated with positive schizotypy. Furthermore, the deficits were selective to the recognition of similar lures in the MST.…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe similar deficits with positive schizotypy, or in the interactions of positive schizotypy with the other dimensions. This is in contrast to Vass et al (2022), but consistent with our previous finding that hippocampal volume and episodic memory deficits were not associated with positive schizotypy. Furthermore, the deficits were selective to the recognition of similar lures in the MST.…”
Section: Discussionsupporting
confidence: 92%
“…Koller and Cannon (2021) and Sahakyan and Kwapil (2019) demonstrated that paranoia and positive schizotypy, respectively, were associated with impaired novelty detection (i.e., false recognition), suggestive of overactive retrieval writ large. Yet another study showed positive schizotypy to be associated with an improved ability to correctly reject similar lures (Vass et al, 2022); still another suggested no such association (Kraguljac et al, 2018). Our results are in line with a more nuanced model of novelty-related impairment among paranoid individuals: Even when novelty is detected, it less effectively triggers the typical shift toward an “encoding mode,” via pattern separation (vs. a “retrieval mode,” via pattern completion).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this may result in spurious retrieval events that fuel the aberrant associations characteristic of delusions, insofar as they encourage connections between a current experience and a (weakly related) past representation instead of facilitating new learning (Koller & Cannon, 2022;Tamminga et al, 2010). However, prior findings are in conflict as to whether psychosis spectrum individuals show such a systematic memory bias (Das et al, 2014;Kraguljac et al, 2018;Martinelli & Shergill, 2015;Vass et al, 2022), pointing to a more nuanced relationship between positive symptoms and novelty detection.…”
mentioning
confidence: 99%
“…This observation is consistent with prior studies that assessed item and response type interactions in people with schizophrenia 29 , 30 , first-episode psychosis 28 , and elevated negative and disorganized schizotypy 39 . However, at least one study has demonstrated lower false alarm rates of lure items in people with high positive schizotypy symptoms 40 , which can predict schizophrenia spectrum disorders 41 . Taken together, the current findings are consistent with prior research that has demonstrated a selective inability to identify lure items as similar in non-developmental populations.…”
Section: Discussionmentioning
confidence: 99%